Apprentice in Death - Robb, J. D., 1950- (New York: Brilliance Audio Inc., 2016)
Within seconds, three random people were shot dead at Central Park's ice skating rink. After reviewing security videos, it becomes clear that the victims were killed by a sniper firing a tactical laser rifle, who could have been miles away when the trigger was pulled. And though the locations where the shooter could have set up seem endless, the list of people with that particular skill set is finite: police, military, professional killer.
Keywords: Dallas, Eve (Fictitious character) -- Fiction; Policewomen -- New York (State) -- New York -- Fiction; Mystery fiction; Suspense fiction; Detective and mystery fiction; Electronic books